2010
DOI: 10.1148/radiol.10100485
|View full text |Cite
|
Sign up to set email alerts
|

Low Yield of Chest Radiography in a Large Tuberculosis Screening Program

Abstract: 1Ronald L. Eisenberg , MD Nira R. Pollock , MD , PhD Purpose:To assess the frequency and spectrum of abnormalities on routine screening chest radiographs in the pre-employment evaluation of health care workers with positive tuberculin skin test (TST) results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 8 publications
3
27
1
Order By: Relevance
“…Our findings contrast with two studies in adults in which CXR screening failed to identify any cases of active TB among asymptomatic healthcare workers 7 8. However, an important difference between these studies in adults and our study is that our patients had a TST/IGRA as a result of identified risk factors for TB, whereas the previous studies screened low-risk populations.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our findings contrast with two studies in adults in which CXR screening failed to identify any cases of active TB among asymptomatic healthcare workers 7 8. However, an important difference between these studies in adults and our study is that our patients had a TST/IGRA as a result of identified risk factors for TB, whereas the previous studies screened low-risk populations.…”
Section: Discussioncontrasting
confidence: 99%
“…Features suggestive of active TB (defined as cavitation, consolidation, pleural effusion and miliary disease) or prior TB (defined as pleural thickening, fibrous scarring, calcified lymph node and calcified granuloma) were documented 7. Non-calcified hilar lymphadenopathy was documented as a separate category.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By our observation fibrocalcified lesions should be evaluated for active TB specifically in this era which the prevalence of patients with active TB presented with atypical manifestations is increasing (24). Besides, patients with these manifestations are ignored even though they are a reservoir for distributing M. tuberculosis (25). So we suggest that not only the patients with unexplained productive coughs for more than 2-3 weeks, but also patients with other symptoms or even without symptoms or typical radiological findings, but with apical fibrocalcification would be be evaluated for active TB by sputum analysis and bronchoalveolar lavage if the result of sputum was negative, especially in endemic areas such as our country.…”
Section: Discussionmentioning
confidence: 72%
“…Although there were 108 cases with calcification or fibrosis out of the total 159 with abnormal findings in CXR, they didn't find any criteria for active TB in radiology. As they mentioned they didn't try for acid fast bacilli in calcified or fibrotic lesions, though they tried it in noncalcified nodules (25).…”
Section: Discussionmentioning
confidence: 99%